Pengaruh Self-Regulated Learning Terhadap Kemampuan Berpikir Kritis dan Hasil Belajar Siswa - Mahrufah, Menik; Rijanto, Tri (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2024)
This study aims to analyse the influence of self-regulated learning on students' critical thinking skills and learning outcomes. Self-regulated learning is the ability of students to manage their learning process independently, including setting goals, monitoring, and evaluating learning achievements. This ability is considered an important factor in improving critical thinking skills, which involves analysing, evaluating, and making decisions based on relevant evidence. The research was conducted using a quantitative method with a correlational approach to upper secondary students. The results showed that there was a positive and significant influence between self-regulated learning on critical thinking skills and student learning outcomes. Students who have a high level of self-regulated learning tend to be better able to critically analyse problems and achieve better learning outcomes. These findings show that the development of self-regulated learning needs to be the focus of learning strategies, to encourage continuous improvement of learning quality and support students in facing academic challenges in the modern era.